Treatment with 815-nm diode laser induces long-lasting expression of 72-kDa heat shock protein in normal rat skin - Souil, E.; Capon, A.; Mordon, S.; Dinh-Xuan, A.T.; Polla, B.S.; Bachelet, M. (British journal of dermatology (1951), 2001)
Background We previously reported that skin closure is improved by photoirradiation of the wound margins with an 815‐nm diode laser system. Objectives To determine whether the beneficial effects of laser treatment involve the overexpression of the inducible 72‐kDa heat shock protein, Hsp70. Methods Expression of Hsp70 was investigated by immunocytochemistry in normal hairless rat dorsal skin and compared with its expression after laser photoirradiation. Results Constitutive expression of Hsp70 was mainly confined to the upper epidermal layer. Laser irradiation further increased epidermal expression of Hsp70 while inducing de novo synthesis of the protein in dermal structures, particularly around blood vessels, hair follicles and sebaceous glands. Laser‐induced expression of Hsp70 was still present 7 days after photoirradiation. Conclusions Laser‐induced expression of Hsp70 might contribute to improved tissue regeneration and wound healing.